Effects of Ethephon Doses and Application Times on Yield and Yield Components of Chickpea Cicer arietinum L. - Mustafa Güler (Journal of Agricultural Sciences)
This study was conducted in the growing seasons of 2006-2007 and 2007-2008 to determine the effects of different ethephon doses and application times on yield and yield components of chickpea. Gökçe cultivar of chickpea was used as material in the study, and 0,150, 300, 450 and 600 g/ha ethephon doses were applied at the growth stages of three-leaves stage, before anthesis and grain filling period. Results of the study indicated that significant effects were determined with the application of different ethephon doses and application times in the traits of chickpea. The effect of ethephon application times on grain yield were nonsignificant, and the highest grain yield was obtained from the 450 g/ha ethephon dose. Ethephon application positively affected most of yield components in chickpea, and the greatest values were determined with the ethephon applications before anthesis